Comprehensive Assessment of the Agriculture Sector in Liberia : Volume 2, Sub-sector Reports, Part I - Ministry of Agriculture (Liberia) (2012)
The overall objective of the Comprehensive Assessment of the Agricultural Sector (CAAS) is to provide an evidence base to enable appropriate strategic policy responses by the Government of Liberia (GoL) and its development partners in order to maximize the contribution of the agriculture sector to the Government's overarching policy objectives. Given the strong relationship between growth in agricultural productivity and poverty reduction, future efforts in Liberia need to focus on productivity enhancing measures with a pro-poor focus that increase incomes. Growth based on extensification using traditional technologies is generally not profitable and has damaging implications for the environment. Given the low level of assets possessed by most Liberians, future efforts need to address the question of access to assets (i.e. land, knowledge and inputs) in addition to providing opportunities and an enabling environment. Liberia needs to make concerted efforts to preserve and consolidate its emerging stability by focusing on interventions to ensure food security and poverty alleviation at the community and household levels. Improving access to food and generating sustainable, remunerative activities and employment are crucial to this process. This report is designed to assist in indicating and specifying the potential role of specified agricultural commodity value chains in achieving the priority objectives of the government by focusing on small holders, traditional farming, and food security and forms an input for the preparation of a strategic orientation framework to achieve sustainable food security, nutrition and agricultural development. This report reviews gender issues in Liberia's agriculture and rural sector with a special focus on rural women and how to improve their participation and contribution to rural development. The report reviews women's roles in agriculture and the rural economy; their access to key inputs and services which are essential to carry out their socio-economic role in rural areas; as well as gender-related social trends and problems that may have an impact on productivity and poverty reduction in rural areas. The assessment also reviews the institutional and policy framework for agriculture and rural development and identifies opportunities to improve the rural sector's capacity to address gender issues and support female farmers and rural entrepreneurs. The findings and recommendations will inform the reform of the sector, currently underway, and thereby support the GoL poverty reduction effort and the implementation of the Interim Poverty Reduction Strategy Paper (IPRSP).